Impaired spatial coding of the hippocampus in a dentate gyrus hypoplasia mouse model - Xiaojing Chen; Ning Cheng; Cheng Wang; James J. Knierim (Proceedings of the National Academy of Sciences, 2025)
The hippocampal dentate gyrus (DG) is thought to orthogonalize inputs from the entorhinal cortex (pattern separation) and relay this information to the CA3 region. In turn, attractor dynamics in CA3 perform a pattern completion or error correction operation before sending its output to CA1. In a mouse model of congenital hypoplasia of the DG, a deficiency in the Wntless (Wls) gene, specifically in cells expressing Gfap-Cre , which targets neuronal progenitors, led to an almost total absence of dentate granule cells and modestly impaired performance in spatial tasks. Here, we investigated the physiological consequences of granule cell loss in these mice by conducting in vivo calcium imaging from CA1 principal cells during behavior. The spatial selectivity of these cells was preserved without the DG. On a linear track, place fields in mutant mice were more likely to be near track terminals and to encode the distance from the start point in each running direction. In an open box, CA1 cells in mutant mice exhibited reductions in the percentage of place cells, in spatial information, and in place field stability. The reduction in place field stability across repeated exposures to the same environment resulted in a reduction in the differential representations of two different contexts in mutant mice compared to wild-type mice. These results suggest that DG helps to stabilize CA1 spatial representations, especially in 2-D environments, and that the lack of stability across similar environments may play a key role in the deficits of animals with DG dysfunction in discriminating different environments.